2020
DOI: 10.1039/d0ob00519c
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic-biology-based discovery of a fungal macrolide from Macrophomina phaseolina

Abstract: Genome mining and heterologous biosynthesis led to the discovery of a 12 membered macrolide from Macrophomina phaseolina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Phanerochaete chrysosporium is a decomposer in carbon cycle [93]. Macrophomina phaseolina produced macrolide [94]. These results suggested that the microbial network topology structure and composition were substantially shaped in the M. incognita-infested soils in this mountain ecosystem.…”
Section: Discussionmentioning
confidence: 78%
“…Phanerochaete chrysosporium is a decomposer in carbon cycle [93]. Macrophomina phaseolina produced macrolide [94]. These results suggested that the microbial network topology structure and composition were substantially shaped in the M. incognita-infested soils in this mountain ecosystem.…”
Section: Discussionmentioning
confidence: 78%
“…mandshuricum ( Xixin ) with synchrotron radiation and 1 . Most recently, Morishita, Fujita, et al solved phaseolide A ( 22 ), a 12-membered macrolactone genomically mined from Macrophomina phaseolina , using the Cl congener of 1 . For metabolite analysis, Fujita et al coupled HPLC with 1 to analyze reductive reactions on organic compounds by Saccharomyces cerevisiae .…”
Section: Diversity Of Crystalline Matricesmentioning
confidence: 99%
“…Despite the immense potential of the method and recent improvements and successes (Hoshino et al, 2016;Hayes et al, 2016;Ramadhar et al, 2015a,b;Easun et al, 2017;Cuenca et al, 2016;Cardenal & Ramadhar, 2021;Bosch et al, 2014;Goh et al, 2018;Inokuma et al, 2016Inokuma et al, , 2014Kersten et al, 2017;Lee et al, 2017;Li et al, 2019;Matsuda et al, 2016;Mitsuhashi et al, 2018;Morishita et al, 2020;Morita et al, 2020;Rissanen, 2017;Vinogradova et al, 2014;Wada et al, 2018;Waldhart et al, 2016;Yoshioka et al, 2016;Yuan et al, 2019;Zigon et al, 2015;de Poel et al, 2019;Urban et al, 2016;Sakurai et al, 2017) it is still far from being the universal way to determine the structure of troublesome compounds, because the method still faces some serious challenges: the time-consuming process of analysis is highly dependent on the analytes and must be carried out in separate batches for each sample. The obtained crystal structures are often crystallographically challenging because of the nature of the particular host-guest interactions (Cardenal & Ramadhar, 2021;Hoshino et al, 2016;Zigon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%